Manufacturing productivity under varying trade regmies: India in the 1980s and 1990s - Deb Kusum Das (Indian Council for Research on International Economic Relations (ICRIER), 2003)
The paper examines productivity performance of Indian manufacturing under varying trade regimes.The standard growth accounting methodology is applied to data compiled from the Annual Survey ofIndustries for selected 3-digit use-based manufacturing sectors over the period 1980-2000. The analysisfocuses on the overall period and four sub periods (1980-85, 1986-90, 1991-95 and 1996-00) to reflectthe shifts in trade policy regime. There is no evidence of much change in total factor productivitygrowth following liberalization of the regime initiated in the early 1990s. As in the 1980s, factoraccumulation rather than productivity growth accounts for most of the output growth during this period
Keywords: 330